2002
DOI: 10.1080/01650250143000247
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and generalisability in developmental research: Comparison of random and convenience samples of older adults

Abstract: Researc h in the developmental sciences is based largely on samples of convenience rather than samples drawn at random from the population. The important question of whether results observed in samples of convenience generalise to the larger population has not been studied directly. Because of demographic growth in the proportion of older adults in the population and increases in diversity across the lifespan, it is especially important to address this issue in aging adults. We compared the performance of olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 25 publications
3
83
1
3
Order By: Relevance
“…These include careful attention to selecting and documenting the characteristics of the sample (e.g., age, health), the design (e.g., testing interval, sample size) and the measures (e.g., multiple indicators). We are aware of one other recent study that has addressed this issue (see Hultsch, MacDonald, Hunter, Maitland, & Dixon, 2002). Although cross-sectional in design, these authors reported few significant differences when contrasting demographic and psychological performance of older adults from a random sample versus two samples of convenience.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These include careful attention to selecting and documenting the characteristics of the sample (e.g., age, health), the design (e.g., testing interval, sample size) and the measures (e.g., multiple indicators). We are aware of one other recent study that has addressed this issue (see Hultsch, MacDonald, Hunter, Maitland, & Dixon, 2002). Although cross-sectional in design, these authors reported few significant differences when contrasting demographic and psychological performance of older adults from a random sample versus two samples of convenience.…”
Section: Discussionmentioning
confidence: 90%
“…Although cross-sectional in design, these authors reported few significant differences when contrasting demographic and psychological performance of older adults from a random sample versus two samples of convenience. Specifically, Hultsch et al (2002) observed no differences on word list recall between the random sample and the convenience sample recruited for a study of memory and aging. Further research will examine the extent to which generalizability across samples applies to longer term normal memory aging or to transitional phases of impaired cognitive aging.…”
Section: Discussionmentioning
confidence: 99%
“…Typical approaches to sampling to maximise generalisability of findings in longitudinal studies are use of smaller population frames, such as specific regions or cities, development of structured samples of convenience and selection of an explicitly biased sample. 16 All three approaches were combined into this study's regional recruitment strategy as previously described.…”
mentioning
confidence: 99%
“…Kemudian teknik pengumpulan sampel yang digunakan dalam penelitian ini adalah convenience sampling. Pengambilan sampel secara convinience mengarahkan pada pengambilan sampel secara nonrandom (Hultsch, MacDonald, Hunter, Maitland, & Dixon, 2002;Onwuegbuzie & Collins, 2007). Pemilihan metode pengambilan sampel ini dikarenakan pada saat proses penelitian tidak semua sampel mau mengisi kuisioner dan bersedia menjadi kuisioner.…”
Section: Metode Penelitianunclassified